Penerapan Alat Peraga Torso untuk Meningkatkan Hasil Belajar Siswa pada Pembelajaran Organ Tubuh Manusia di Kelas V Sekolah Dasar Negeri 105386 Tanjung Siporkis - Shafira Aulia Rahmah; Layil Safitri; Astria Ayu Ramadianti (Medan Resource Center, 2025)
This study was conducted in response to the limited use of instructional teaching aids in elementary science classrooms, which has contributed to low student engagement and unsatisfactory learning outcomes in the topic of human body organs. The study aimed to investigate whether the application of torso teaching aids could improve students’ learning outcomes in learning human organ systems. Employing a classroom action research design, data were collected through classroom observations, learning achievement tests, and documentation. The research was implemented in two instructional cycles involving fifth-grade students at Sekolah Dasar Negeri 105386 Tanjung Siporkis. Data were analyzed using descriptive quantitative techniques to examine changes in students’ learning achievement across cycles. The findings revealed a substantial improvement in students’ learning outcomes, with classical mastery increasing from 33.33% in the pre-cycle stage to 86.67% by the end of the second cycle following the use of torso teaching aids. These results demonstrate that torso-based instructional media effectively enhance students’ conceptual understanding and learning performance in human body organ lessons. The study concludes that the integration of concrete teaching aids is a pedagogically effective strategy for improving science learning outcomes at the elementary school level.